Akuntansi Sosial: Social Return On Investment (SROI) Sebagai Wujud Instrumen Dalam Menilai Dampak Dan Keberlangsungan Bisnis - Anugrah, Audito Aji (Fakultas Ekonomi Prodi Akuntansi, 2024)
This research aims to discuss the Social Return on Investment (SROI) process as a form of social accounting perspective. This research provides a framework of viewpoints related to Social Return on Investment (SROI) as an instrument in assessing the impact of business sustainability and measuring the impact of social and environmental aspects of business activities. The research method used is qualitative with an interpretive approach. Research was carried out by collecting research articles, books and other electronic media on topics related to Social Accounting. The results of this research show that Social Return On Investment (SROI) plays the role of social accounting as a business language link to communicate to stakeholders regarding the social and environmental aspects of the company's business. SROI has the advantage of helping assess and explain the dynamics of the impact of changes in social aspects and the business environment which are realized through calculating Ratios, Theory of Change and Story of Change. Therefore, companies can provide legitimacy to the business they run through implementing SROI on social and environmental impacts.